Reply to the Comments on Epistemic Ambitions of the Criminal Trial: Truth, Proof and Rights - Sarah Jane Summers (Quaestio Facti, 2024)
This article sets out to reply to the comments by Antony Duff, Sabine Gless, John Jackson and Thomas Weigend on my article «Epistemic Ambitions of the Criminal Trial». It begins by examining the various positions of the commentators to the question of the aim(s) of the criminal trial before going on to consider the limits of instrumentalist and proceduralist approaches and to re-examine the right-based conception of trials. It concludes by considering the implications of this account of criminal trials.